Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.3382/ps.0570080
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Progressive Versus Regressive Rous Virus-induced Avian Sarcomas According to Tumor and Infiltrating Lymphocyte Fine Structure , ,

Abstract: Electron microscope examination of progressing and regressing Rous virus-induced sarcomas in an inbred line of White Leghorns revealed that regressing tumors contained moderate to marked lymphocyte infiltration, frequent contact between lymphocytes and tumor cells, and extensive areas of necrosis. Lymphocytes infiltrating regressing tumors exhibited a polar accumulation of organelles at the point of contact between lymphocyte and target cell. On the other hand, progressing tumors contained low to moderate numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Controversy, however, exists about the participation of other cell types. Histopathological observations in both chickens (Stenkvist and Ponten, 1963;Perry et al, 1978) and quails (Yoshikawa et al, 1975) have implicated the lymphocyte as the major infiltrating cell type. It has been suggested, therefore, that macrophages function as mere scavengers in the ASV-system without participating in the anti-tumor defense.…”
Section: Introductionmentioning
confidence: 97%
“…Controversy, however, exists about the participation of other cell types. Histopathological observations in both chickens (Stenkvist and Ponten, 1963;Perry et al, 1978) and quails (Yoshikawa et al, 1975) have implicated the lymphocyte as the major infiltrating cell type. It has been suggested, therefore, that macrophages function as mere scavengers in the ASV-system without participating in the anti-tumor defense.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that tumor-infiltrating lymphocytes are present in tumor tissues and play an important role in tumor development, regression, and treatment in cancer patients [147][148][149]. Adoptive cell therapy with TIL in combination with cyclophosphamide and IL-2 cured advanced hepatic metastases and pulmonary metastases in mice [150].…”
Section: Tumor-infiltrating Lymphocyte (Til) Therapymentioning
confidence: 99%